Factors Predicting Adverse Events Associated with Pregabalin Administered for Neuropathic Pain Relief - Yuko Kanbayashi; Keiko Onishi; Toyoshi Hosokawa (Pain Research and Management)
BACKGROUND:Pregabalin administration is occasionally abandoned due to adverse events such as somnolence, dizziness, unsteadiness, weight gain and edema. However, the exact causes of these differences in adverse events associated with pregabalin have not been elucidated.